Developing local film production in Indonesia: tactical hustling among Yogyakarta film practitioners, 2000-2019 - Suwarto, Dyna (2024)
Indonesia’s political reformation of 1998 and afterwards, resulted not only in the end of President Suharto’s decades of authoritarian rule, but also stimulated rapid growth and cultural contestation within the country’s film industry. Diverse film cultures proliferated throughout the archipelagic nation. One of the most important sites of this cultural contestation through film emerged in the Special Region of Yogyakarta Province. While local film culture in Yogyakarta has a history dating from the 1940s, the period between 2000-2019 was a key period of transformation, and saw the development of a distinct production culture where dynamics of amateurism and professionalism, informality and formality, collaboration and creative precarity, defined film practice.